Characterizations of those Pn(S) which are Relatively Stone Nearlattice - Akhter, S.; Noor, A. S. A. (Journal of Scientific Research, 2012)
For a fixed element n of a nearlattice S, a convex subnearlattice of S containing n is called an n-ideal of S. An n-ideal generated by a single element a is called a principal n-ideal, denoted by n. The set of principal n-ideals is denoted by Pn(S). A distributive nearlattice S is called relatively Stone nearlattice if each closed interval [x,y] with is a Stone lattice. In this paper, we give several characterizations of those Pn(S) which are relatively Stone in terms of n-ideals and relative n-annihilators. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.10103 J. Sci. Res. 4 (3), 589-601 (2012)